Relationship Building, Collaboration and Flexible Service Delivery: The Path to Engagement of Refugee Families and Communities in Early Childhood Trauma Recovery Services. (14th September 2017) - Signorelli, R. G.; Gluckman, N. S.; Hassan, N.; Coello, M.; Momartin, S.
Abstract : Service utilisation by refugee families may be affected by the mismatch between Western individualistic service delivery approaches and the target communities' more collectivist cultural patterns and practices. In addition to access barriers, utilisation of early childhood services by refugees can also be impacted upon by distrust of services, health and settlement issues, stigma, unfamiliarity with early childhood programmes, and fear of child protection and other legal systems. This low service utilisation sits in conflict with the need for early interventions for very young children, who are in the peak period of brain development. This article explores the implementation of a model to address these issues in early childhood work with refugee families and communities, with the intent to increase service uptake. Some strategies to address potential barriers will be described in the context of a community engagement model that includes consultation, relationship building, collaborative flexible service design and delivery, partnerships in community capacity building and cross-referral. Flexible, culturally appropriate interventions can enhance strengths based, non-pathologising and development-focused approach. A community engagement approach will, nevertheless, present challenges for service providers who must be willing to adapt their practices. Services and funding bodies need to recognise that this process is lengthy and resource intensive, but will ultimately lead to better service delivery and uptake, potentially leading to improvements in health, development and relational outcomes, for children and families from refugee backgrounds.